2018
DOI: 10.1021/jacs.8b10176
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Electrochromic Materials as Activatable Probes for Molecular Imaging and Photodynamic Therapy

Abstract: Electrochromic materials (EMs) are widely used color-switchable materials, but their applications as stimuli-responsive biomaterials to monitor and control biological processes remain unexplored. This study reports the engineering of an organic π-electron structure-based EM (dicationic 1,1,4,4-tetra­aryl­buta­diene, 1 2+) as a unique hydrogen sulfide (H2S)-responsive chromophore amenable to build H2S-activatable fluorescent probes (1 2+-semiconducting polymer nanoparticles, 1 2+-SNPs) for in vivo H2S detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(117 citation statements)
references
References 72 publications
0
117
0
Order By: Relevance
“…In 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 this geometry, two MHB + chromophores can be stacked to each other with the shortest CÀ C contact of 3.01(2) Å. The Zconfiguration of the dication was previously found in 1 a 2 + (I 3 À ) 2 [torsion angle: 19.8(5)°, contact 2.88(1) Å] [ 9,16] or 2 a 2 + (BF 4 À ) 2 [torsion angle: 15.4(4)°, contact 3.018(5) Å]. [20] Preliminary analysis on 3 b 2 + (BF 4 À ) 2 also shows Z-configuration (Figure 4d).…”
Section: Molecular Structures Of Diene and Dicationmentioning
confidence: 86%
See 3 more Smart Citations
“…In 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 this geometry, two MHB + chromophores can be stacked to each other with the shortest CÀ C contact of 3.01(2) Å. The Zconfiguration of the dication was previously found in 1 a 2 + (I 3 À ) 2 [torsion angle: 19.8(5)°, contact 2.88(1) Å] [ 9,16] or 2 a 2 + (BF 4 À ) 2 [torsion angle: 15.4(4)°, contact 3.018(5) Å]. [20] Preliminary analysis on 3 b 2 + (BF 4 À ) 2 also shows Z-configuration (Figure 4d).…”
Section: Molecular Structures Of Diene and Dicationmentioning
confidence: 86%
“…Dication 1 a 2+ was found to react efficiently with H 2 S over endogenous reducing agents (e. g., glutathione, L ‐cysteine and vitamin C) in cells to give 1 a . The large difference in the absorption spectra between 1 a 2+ and 1 a can be used for the OFF/ON switching mechanism of detection, and the activatable probe for non‐invasive and real‐time detection of H 2 S was successfully constructed based on the EM of 1 a / 1 a 2+ …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9C). In addition, Wu et al 100 reported a class of H 2 S-activated uorescent probes and photodynamic smart reagents using electrochromic materials (EMs) with organic p-electron structure (dicationic 1,1,4,4-tetraphenylbutadiene, 1 2+ ) as H 2 Sresponsive chromophores. EM1 2+ is doped into semiconductor polymer nanoparticles (SNPs) to form H 2 Sactivatable uorescent probes (1 2+ -SNPs) (Fig.…”
Section: Photodynamic Therapymentioning
confidence: 99%